State-of-the-art and future trends in electric vehicle charging infrastructure: A review - Sudev V.; Sindhu M.R. (Engineering Science and Technology, an International Journal)
In this era of global warming and climate change, the trend towards “GO GREEN” is gaining significant attention because of its advantages for the world in general and society in particular. One of the most significant aspects of this “GO GREEN” is the sustainable mobility sector, which focuses not only on reducing the usage of fossil fuels but also on enhancing the efficiency of the transportation system. The most critical infrastructure required in the sustainable transportation ecosystem is the Electric Vehicle Charging Stations (EVCS) as it plays a crucial role in increasing the acceptance of Electric Vehicles (EVs). However, a detailed study of the existing EVCS infrastructure is vital for further deepening the research in this area so that future EVCS infrastructure can be developed by overcoming current shortcomings and addressing the needs of the EV ecosystem. Given this fact, this paper investigates in detail the significant aspects, current progress, and future trends associated with the EVCS and its sub-units like power converters, Energy Storage Systems (ESS), charging technologies, etc. This paper primarily focuses on the power converters and the charging technologies as this forms the ‘heart’ of an EVCS, while also elaborating on other associated topics like ESS, EVCS classification, etc. This paper also discusses in detail the issues faced while charging EVs in extreme weather conditions by considering the case of EVs not charging in Chicago in January 2024 and also discusses how the new charging techniques like Constant Current Constant Temperature Constant Voltage (CCCTCV) can help in overcoming such issues. Various important papers in these areas, their contributions, and shortcomings are deliberated in this paper. This paper also highlights the important power converter topologies and charging technologies, their features, characteristics, advantages and disadvantages, and their application scope in the EV ecosystem. The combination of conventional power converters with advanced control techniques, dynamic charging techniques, and post-Li-ion ESS will help in building a futuristic, reliable, and resilient EVCS infrastructure.